Religion and Economic Ethics in Encouraging Economic Growth - Mardani, Dede Aji; Muhamad Zainul Abidin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
As a city of santri, Tasikmalaya is also known as a city with high economic growth in the eastern priangan region. The aim of this research is to analyze the value of religious values as economic growth triggers in Tasikmalaya. The method used is qualitative with interview data collection techniques from various sources who have a Muslim entrepreneur background. The research results show that there are transcendent and prophetic values practiced by entrepreneurs. Economic ethics practiced by traders plays a very significant role in encouraging economic behavior (homo religious towards homo economicus). The economic ethics practiced are honesty, product certainty (warranty), keeping promises, diligent charity, and faith in the last day. Meanwhile, the values and ethics of traders are obtained from the holy book Al-Quran and Hadith, religious leaders, recitations, this proves that religious values and ethics are proven to improve economic growth.